Kemampuan Membaca Arab Melayu Anggota LSMI Al-Mizan FH UNRI 2022 - Hasnah Faizah; Nurhaliza Nurhaliza (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine and describe the reading ability of Malay Arabic members of the Al-Mizan Islamic Student Study Institute FH UNRI 2022. The method used in this research is the description method with a sample of 27 Student Members of the LSMI Al-Mizan FH UNRI 2022. The data collection technique used in this research is the test technique using google form. The research data analysis technique of this research is quantitative . The results of the study concluded that the ability to read Arabic-Malay discourse varied, namely 1. Fluent; 2. Moderate; 3. Low. The ability to read Malay Arabic discourses of LSMI Al-Mizan FH UNRI members has a high category of 94.62 and a category of ability to determine open syllables + closed syllables and open syllables + Malay Arabic open syllables in a low-category Anecdotal Text with an average of 58.05.